Development of spray-dried amorphous solid dispersions of tadalafil using glycyrrhizin for enhanced dissolution and aphrodisiac activity in male rats - Mohammed Muqtader Ahmed; Farhat Fatima; Mohd Abul Kalam; Aws Alshamsan; Gamal A. Soliman; Abdul Azim Shaikh; Saad M Alshahrani; Mohammed F. Aldawsari; Saurabh Bhatia; Md. Khalid Anwer (Elsevier, 2020)
Tadalafil (TDL) is a phosphodiesterase-5 inhibitor (PDE5I), indicated for erectile dysfunction (ED). However, TDL exhibits poor aqueous solubility and dissolution rate, which may limit its application. This study aims to prepare amorphous solid dispersion (ASD) by spray-drying, using glycyrrhizin-a natural drug carrier. Particle and physicochemical characterizations were performed by particle size, polydispersity index measurement, yield, drug content estimation, Fourier Transformed Infrared (FTIR) spectroscopy, Differential scanning calorimetry (DSC), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and dissolution study. In order to evaluate the aphrodisiac activity of the prepared ASD, sexual behavior study was performed in male rats. It is further considered for the stability study. Our results revealed that TDL-GLZ spray-dried dispersion was a successful drug-carrier binary mixture. XRD and SEM showed that ASD of TDL with GLZ presented in the amorphous state and dented-spherical shape, unlike the drug indicating crystalline and spiked shaped. The optimized ASD3 formulation with particle size (1.92 µm), PDI (0.32), yield (97.78%) and drug content (85.00%) showed 4.07 folds' increase in dissolution rate compared to pure TDL. The results obtained from the in vivo study exhibit significantly improved aphrodisiac activity with ASD3. The stability study revealed that the prepared ASD3 did not show any remarkable changes in the dissolution and drug content for 1 month storage at room temperature.